Management of Software Engineering Innovation in Japan - Kadono, Yasuo; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2015)
This book assesses the achievements of the software engineering discipline as represented by IT vendors in Japan in order to deepen understanding of the mechanisms of how software engineering capabilities relate to IT vendors$1 (Bbusiness performance and business environment from the perspective of innovation and engineering management. Based on the concepts of service science and science for society, the volume suggests how to improve the sophistication of services between the demand side, i.e., IT user companies, and the supply side, i.e., IT vendors, simultaneously. The author and his colleagues developed a structural model including innovational paths, such as service innovation, product innovation and process innovation, and a measurement model including the seven software engineering capabilities: deliverables, project management, quality assurance, process improvement, research and development, human resource development, and customer contact. Then they designed research on software engineering excellence and administered it with the Japanese Ministry of Economy, Trade and Industry and Information-Technology Promotion Agency. Through statistical analyses of the results, they found that human resource development and R&D are significant fundamental conditions to improve the quality of the deliverables and that IT firms with high levels of deliverables, derived from high levels of human resource development, quality assurance, project management and process improvement, tend to sustain high profitability. In addition, they developed a measurement model based on Porter$1 (Bs five forces and Barney$1 (Bs resource-based view. A regression tree analysis suggested that manufacturer spin-off vendors tend to expand business with well-resourced R&D, whereas user spin-off vendors tend to depend heavily on parent company demand.s
Part I Industry and Engineering Capabilities from Surveys and Statistical Analyses -- 1.Introduction to Software Engineering Innovation in Japan -- 2. Surveys on Software Engineering Excellence -- 3. Statistical Analysis Results and Practical Implications of the SEE Surveys -- Part II Research Relevant to Managing Innovation in the Broadest Sense -- 4. A Study of the Characteristics of Software Vendors in Japan from a Competitive Environment and Resource-Based Viewpoint -- 5. IT Management Effectiveness: An Empirical Study in Japanese Companies -- 6. Social Research on IT Management Innovation Toward Service Science and Science for Society -- 7. Agent-Based Modeling of the Software Industry Structure in Japan: Preliminary Consideration of the Influence of Offshoring in China -- 8. Hybrid Methods to Predict Scenarios in the Japanese Software Industry.
Keywords: Business; Management; Industrial management; Industrial procurement; Business and Management; Innovation/Technology Management; Procurement; Electronic books